Strategies for improved feed utilisation and ruminant production systems in the Asian region - Devendra, C. (AAAP, 2000)
Strategies for improved feed utilisation and ruminant production systems are discussed in the context of the demand-led processes for foods of animal origin, in which the contribution of ruminants is lagging. Increased productivity in the future will need to come from improved per animal performance, and the under utilised but potentially important rainfed land areas. Increased resource use is necessary and there is a need to target ruminant production systems and the opportunities to improve productivity, in mixed farm systems. Prevailing ruminant production systems are unlikely to change in the forseable future, and the principal aim should therefore be to intensify the use and efficiency of the feed resources, in which the benefits should be identified with self-reliance in the use of feeds, sustainable agriculture and environmental integrity.